Pengaruh Model Pembelajaran Experiential Learning dengan Studi Kasus terhadap Kemampuan Berpikir Kritis Siswa pada Materi Sistem Reproduksi Manusia - Siti Neng Mariyam; Sri Dwiastuti; Puguh Karyanto (BIO-PEDAGOGI, 2014)
The aim of this research was to investigate the influence of the learning model of Experiential Learning with case study of students' critical thinking skills in the human reproductive system material.Research is Quasi Experiment (quasi-experimental) with research design Posttest Only with Non-equivalent Control Group Design. The research population was all students of eleventh (XI) grade IPA SMA Negeri 6 Surakarta academic year 2012/2013. Sampling technique in the study is cluster sampling, with samples of the two classes, there are eleventh grade (XI) IPA 1 with 26 students as the number of experimental class and eleventh (XI) IPA 3 with 28 students a class control. Treatment in the experimental class is the application of the learning model of Experiential Learning with case study and in control class applied conventional learning model with varied lectures. The technique of collection data was using test method (essay) and non-test (documentation and observation). Hypothesis testing is done by using a t-test. The results showed that the average value of the critical thinking skills of students in the experimental class was higher than the control class, which is 64.42 in experimental class and 51 in the control class. The results show the significant value of t test is 0.000 (sig. <0.05), so it can be said that there are significant differences in thecritical thinking skills betweenexperimental class with control class. The research has conclusion that the model of experiential learning with case studygives significant effect on students' critical thinking skills for eleventh(XI) grade IPA SMA Negeri 6 Surakarta in academic year 2012/2013 on the matter of human reproductive system. Key Words: experiential learning, learning method in case study, critical thinking skills